Influence of anthropometric characteristics on jumping performance in young basketball players in british basketball leauge - Petrovic, M.; Ramos, J.; Solaja, M.; Golik-Peric, D.; Obradovic, B. (Sport Scientific and Practical Aspects - International Scientific Journal of Kinesiology, 2013)
Talent identification programs have traditionally focused on identifying talented athletes for individual sports with discrete physical and physiological characteristics. Team sports have been less inclined to conduct talent identification and selection programs. It has been thought that success in team sports is more related to knowledge of game strategies and skills as well as performance characteristics, and therefore it may be more difficult to predict potentially talented athletes. The aim of this study was to determine the impact of several anthropometric characteristics on manifestations of explosive leg strength, expressed by three tests (standing long jump, triple jump on left leg and triple jump on right leg). The sample included 23 basketball players (aged 16±1) from Manchester Giants Academy, who were tested. Regression analysis from package SPSS 10.0 was used for data processing. The results showed that anthropometric characteristics do not have a statistically significant impact on the manifestation of explosive leg strength.